The impact of the reconstruction of megablocks (1990–2020) on the quality of common open public spaces: blocks 21 and 28 in New Belgrade - Bulatović, Slobodan (Arhitektura i urbanizam, 2021)
The quality of common open public spaces is conditioned, among other things, by the layout and characteristics of the facilities located in their immediate vicinity, but also by the functions and contents, equipment and materialization of the ground floor of those facilities. For this reason, interventions on existing facilities and the construction of new ones around common open public spaces can positively or negatively affect the quality of these areas. The construction of New Belgrade began in 1948 and continues today. In the area of ​​New Belgrade, the network of common open public spaces covers more than 50% of the total area of the ​​municipality. Initially, the blocks in New Belgrade were built on the basis of a unique planning solution. The transformation of the blocks began in the 1990s in the post-socialist period, when it became possible to change the legal regulations and enable a greater participation of private investments in the processes of reconstruction and new construction. In order to determine the real impact of the reconstruction of mega blocks on the quality of common open public spaces, this paper will present the criteria for determining the quality of these spaces. The criteria will help to examine the differences between the quality of common open public spaces within a block that has had frequent interventions and one where there have been no significant interventions over the last few decades. The conclusions should provide an answer as to whether and to what extent spatial interventions affect the quality of common open public spaces.